Turbulent open-channel flow with upward seepage - Chiew, Yee-Meng (2012)
Measurements of turbulent open-channel flow subjected to an upward bed seepage were performed in a laboratory flume using a two-dimensional Acoustic Doppler Velocimeter and a minipropeller. The experimental results show that the boundary seepage affects the time-mean streamwise velocity, the rms values of the velocity fluctuations, the Reynolds shear stress and the bed shear stress in open-channel flow. Along the seepage zone, the mean streamwise velocity increases much more in the surface layer than that in the near-bed region, whereas the turbulent intensities and Reynolds shear stress increase significantly in the near-bed region. The bed shear stress that was computed using the momentum integral equation shows a steady reduction with increasing upward seepage velocity.